Preparation and thermal properties of shape-stabilized composite phase change materials based on paraffin wax and carbon foam. (10th December 2021) - Wang, Zekun; Zhang, Xiaoguang; Xu, Yunfei; Chen, Guo; Lin, Fankai; Ding, Hao
Abstract: Development of low-cost equipment that can store clean energy, such as solar energy, is effective for alleviating environmental pollution. In this study, the shape-stabilized composite phase change materials (PCMs) based on paraffin wax and carbon foam were prepared. The carbon foam prepared from melamine foam had a good pore structure and was used to encapsulate paraffin wax. The latent heat of melting and cooling of composite PCMs were 221.1 J/g and 213.7 J/g, respectively. Even after 100 cycles, it still showed good thermal performance. Meanwhile, the composite PCMs exhibited good light-to-heat conversion efficiencies of 53.94% and 67.43% at light intensities of 200 mW cm −2 and 300 mW cm −2, respectively. Overall, composite PCMs with excellent thermal performance and cycle stability have application prospects in industries such as construction, solar energy, and battery temperature-control systems. Graphical abstract: Image 1 Highlights: Flexible carbon foams were obtained by annealing melamine foam. Carbon foams with large porosity can be used as a good carrier for PCMs. PW@CF-1300 shows high latent heat and excellent cycle stability. PW@CF-1300 is sensitive to light and can store solar energy.